Effect of sintering temperature and vinca petals extract on structural and magnetic properties of delafossite CuFeO2 - Dhruv, Preksha N.; Solanki, Neha; Kulkarni, Shailja; Jotania, R. B. (International Conference On Condensed Matter and Applied Physics (ICC 2015), 2016)
Delathssite CuFeO2, multi ferroic powder was synthesized using Sol-Gel auto combustion method. Influence of vinea flower petals extract on structural and magnetic properly of CuFeO2 were investigated. X-ray analysis of normal samples (synthesized without presence of vinca petals extract) shows formation of hematite and ferrite phases while the sample synthesized in presence of vinca petals extract show only mono phase. The absorption bands in FTIR spectra present between 510-460 cm(-1)in both the samples are due to stretching of Fe-O vibrations. VSM analysis shows that the squareness ratio (Mr/Ms) of the sample prepared using vinca petals extract obtains value of squareness ratio <0.5, which attributes multi domain formation of samples.
International Conference on Condensed Matter and Applied Physics (ICC), Bikaner, INDIA, OCT 30-31, 2015